Karakter Ganda Penyiar Radio - Puji Laksono (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2016)
Auditory radio broadcasts that rely solely on sounds allow radio broadcasters to present a picture of themselves in different characters with sound only. This means through thevoice of the announcer trying to show self-performance to be able to give an idea to theaudience as if there are different broadcasters in the studio. This research raised a problemabout the self-construction of a broadcasting radio broadcaster in the program of IWT (IstanaWong Tani) at Radio Istana FM Bojonegoro. The theory used is the Phenomenology theory ofAlfred Schutz, Symbolic Interactionism of George Herbert Mead, and Dramaturgy's theory ofErving Goffman. The research method used is qualitative with phenomenology approach. Forthe selection of informants, researchers chose informants deliberating (purposive). Data werecollected through direct observation and in-depth interviews. The validity of the data was doneby using triangulation. The results obtained are the motives of being a radio announcer which consists of themotive of cause, namely a hobby in the world of broadcasting and channeling ideals that arenot achieved the ideals as a puppeteer. Then the motive of the goal is the economic motive, tobe famous, to preserve the Javanese culture and obtain the inner pleasure. As a professionalradio announcer, the demands are to present themselves as best as possible to provide excitingentertainment. As an entertainer, radio broadcasters present themselves in different charactersin their appearance. Double-character radio broadcasters construct themselves in two differentcharacters from self-concept as serious broadcasters and comedian broadcasters. In the eventprogram IWT (Istana Wong Tani), radio broadcasters use verbal symbols to present themselvesdifferently. The symbols used include name, tone of voice, and the use of different Javalanguageson each character. These symbols are as an identity to display different characters.The symbols are as a tool to distinguish each character and change the character according tothe situation. During off-air broadcasting, the dual-character broadcasters use non-verbalsymbols, in the form of costume attributes according to the character to present themselves tobe displayed. Among listeners there is a different perception in judging the appearance ofbroadcasters. Such perceptions can be a praise and a criticism. From these perceptions, thecategory of listeners, the listeners who like a serious broadcaster, listeners who like comedianbroadcasters and listeners who like both.